EVALUATION OF SUPPLEMENTARY FEEDING (PMT) FROM THE GOVERNMENT TO STUNTING TODDLERS - SITI - MARYAM (Journal for Quality in Women's Health, 2022)
Background : This study aims to evaluate the supplementary feeding program for recovery at the Posyandu, Waung Village, Boyolangu District, Tulungagung Regency. Method : This study uses qualitative research methods with purposive sampling of informants. Results : The results of the study indicate that the implementation of this program has not run optimally. Of the four stages that affect the implementation of the program, there are three variables that have not run optimally so that it hampers the implementation of the program. The three things are preparation, including no study of eating patterns and calculation of children's daily needs, no target group of mothers and toddlers and lack of socialization / counseling. Conclution : Suggestions for related agencies, increasing socialization and outreach activities to program targets and increasing supervision on the implementation of the supplementary recovery feeding program